Pengaruh Media Teka-Teki Gambar (TTG) terhadap Hasil Belajar Biologi Materi Struktur dan Fungsi Jaringan Tumbuhan - Anwar, Afifa; Syahriani, Syahriani; Maulana, Andi (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to (1) describe the learning outcomes of students who were taught without using image puzzle (TTG) learning media, (2) describe the learning outcomes of students who were taught using TTG learning media, and (3) examine the effect of TTG learning media on student learning outcomes. This research was quasi-experimental, using a non-equivalent control group design. The population in this study was 341 students of SMA Negeri 2 Pinrang. The sample in this study consisted of 60 students, consisting of 2 classes, namely class XI.1 with 30 students as an experimental class and class XI.2 with 30 students as a control class, which were selected using a purposive sampling technique. The instrument used was a multiple-choice test of 25 items. Both inferential and descriptive statistical data calculations were used in the analysis. The control group, which did not use TTG, had an average posttest learning result of 74.13, which was less than the experimental group's average of 84.80. The significant value of the t-test results was 0.000 <0.05, so it was concluded that there was an influence of the picture puzzle learning media (TTG) on biology learning outcomes in the structure and function of plant tissue material for class XI students of SMA Negeri 2 Pinrang.